Emerging role of mammalian autophagy in ketogenesis to overcome starvation. Issue 4 (2nd April 2016) - Takagi, Ayano; Kume, Shinji; Maegawa, Hiroshi; Uzu, Takashi
ABSTRACT: Autophagy is essential for the survival of lower organisms under conditions of nutrient depletion. However, whether autophagy plays a physiological role in mammals experiencing starvation is unknown. Ketogenesis is critical for overcoming starvation in mammals. We recently revealed that hepatic and renal autophagy are involved in starvation-induced ketogenesis, by utilizing tissue-specific autophagy-deficient mouse models. The liver is the principal organ to regulate ketogenesis, and a deficiency of liver-specific autophagy partially but significantly attenuates starvation-induced ketogenesis. While deficiency of renal-specific autophagy does not affect starvation-induced ketogenesis, mice with deficiency of both liver and kidney autophagy have even lower blood ketone levels and physical activity under starvation conditions than those lacking autophagy in the liver alone. These results suggest that the kidney can compensate for impaired hepatic ketogenesis. Since ketone bodies are catabolized from fatty acids, the uptake of fatty acids, the formation of intracellular lipid droplets, and fatty acid oxidation are critical for ketogenesis. We found that starvation-induced lipid droplet formation is impaired in autophagy-deficient organs. Thus, hepatic and renal autophagy are required for starvation-induced ketogenesis. This process is essential for maintaining systemic energy homeostasis and physical activity during starvation. Our findings provide a novel insight into mammalian autophagy and the physiology of starvation.